A Systematic Literature Review on Chatbot Development For Whatsapp: Programming Language, Method, And Utility - Rahulil, Muhammad; Yuni Yamasari; Ricky Eka Putra; I Made Suartana; Anita Qoiriah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The development of chatbot technology in recent years has shown rapid advancements across various sectors, particularly on popular communication platforms such as WhatsApp. A systematic review is necessary to identify advancements related to chatbot development on WhatsApp. Therefore, this study presents a systematic literature re-view on the development and use of WhatsApp chatbots using the PRISMA framework. From an initial search of 41 studies, followed by filtering according to categories, eight relevant articles were identified from various digital data-bases through focused searches using the keyword